2010
DOI: 10.3390/ph3051335
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs, Opioids, Cannabinoids and the Control of Pain by the Central Nervous System

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) act upon peripheral tissues and upon the central nervous system to produce analgesia. A major central target of NSAIDs is the descending pain control system. The rostral structures of the descending pain control system send impulses towards the spinal cord and regulate the transmission of pain messages. Key structures of the descending pain control system are the periaqueductal gray matter (PAG) and the rostral ventromedial region of the medulla (RVM), both of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 81 publications
10
37
0
1
Order By: Relevance
“…These findings strongly support the suggestion of endogenous opioid involvement in NSAIDs antinociception and tolerance in the descending pain-control system [15-19]. However, involvement of NSAIDs antinociception in the HF is still a matter of controversy.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings strongly support the suggestion of endogenous opioid involvement in NSAIDs antinociception and tolerance in the descending pain-control system [15-19]. However, involvement of NSAIDs antinociception in the HF is still a matter of controversy.…”
Section: Introductionsupporting
confidence: 87%
“…When tolerance develops, PAG microinjections of morphine [32], or metamizol [15], are no longer capable of affecting RVM neurons and inducing analgesia. These results show further neuronal relationships between opioid and non-opioid analgesics as regards the descending pain-control and modulation system [19,30]. In addition, metamizol probably can act via endocannabinoids in the downstream PAG-RVM axis reducing inflammation pain in rats [33].…”
Section: Discussionmentioning
confidence: 79%
“…We have also revealed that repeated microinjections of these nonopioids into the dorsal hippocampus (DH), the nucleus raphe magnus (NRM), and the central nucleus of amygdala (CeA) induce antinociception and the effects of tolerance and cross-tolerance to morphine 8,9,1315. These findings strongly support the suggestion of endogenous opioids involvement in NSAIDs antinociception and tolerance in the descending pain-control system 8,16…”
Section: Introductionsupporting
confidence: 75%
“…According to the recently established concept, the mechanism producing tolerance to NSAIDs can be due to involvement of endogenous opioid peptides 8,16,23,24. In this study, we have clearly shown that pre- and posttreatment of a nonselective opioid receptor antagonist naloxone significantly diminishes NSAIDs-induced antinociception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation